Systematic review of patient-specific pre-operative predictors of pain improvement to endometriosis surgery - Elizabeth Ball; Babu Karavadra; Bethany Jade Kremer-Yeatman; Connor Mustard; Kim May Lee; Sharandeep Bhogal; Julie Dodds; Andrew W Horne; John Allotey; Carol Rivas (Bioscientifica, 2021)
Background: Up to 28% of endometriosis patients do not get pain relief from therapeutic laparoscopy but this subgroup is not defined. Objectives: To identify any prognostic patient-specific factors (such as but not limited to patients' type or location of endometriosis, sociodemographics and lifestyle) associated with a clinically meaningful reduction in post-surgical pain response to operative laparoscopic surgery for endometriosis. Search strategy: PubMed, Cochrane and Embase databases were searched from inception to 19 May 2020 without language restrictions. Backward and forward citation tracking was used. Selection criteria, data collection and analysis: Cohort studies reporting prognostic factors, along with scores for domains of pain associated with endometriosis before and after surgery, were included. Studies that compared surgeries, or laboratory tests, or outcomes without stratification were excluded. Results were synthesised but variation in study designs and inconsistency of outcome reporting precluded us from doing a meta-analysis. Main results: Five studies were included. Quality assessment using the Newcastle-Ottawa scale graded three studies as high, one as moderate and one as having a low risk of bias. Four of five included studies separately reported that a relationship exists between more severe endometriosis and stronger pain relief from laparoscopic surgery. Conclusion: Currently, there are few studies of appropriate quality to answer the research question. We recommend future studies report core outcome sets to enable meta-analysis.